THE ROLE OF PONDOK PESANTREN IN ENCOUNTERING ASEAN ECONOMIC COMMUNITY (AEC) - Ulin Nuha (LPPM IAIN Kudus, 2016)
ASEAN Economic Community (AEC) with characteristics of the economy and labour liberalization can be a blessing for Indonesian people when they are ready to deal with it, but it can also be disastrous if they do not prepare it. This requires the synergy of government and all elements of Indonesian society in facing the ASEAN Economic Community (AEC). Boarding school in the context of history has become an institution that is highly effective not only in the printing community deeply in the science of religion, but also in terms of the economy certainly cannot remain silent in facing the ASEAN Economic Community (AEC).